EEG source imaging analysis of affect using sLoreta - Yaacob, Hamwira Sakti; Abdul Rahman, Abdul Wahab; Kamaruddin, Norhaslinda (2012)
EEG has been widely employed for capturing brain discharge during cognitive activities. However, it is not equipped with a high spatial resolution capability.Thus, a source localization technique is needed for estimating the source of occurrences during brain activities. Commonly, source localization is seen as ‘forward modeling’ and ‘inverse modeling’ problems. An example of source localization tool, sLORETA, was also employed to visualize the brain activation patterns during emotional experiences.